Revamping African and the United States Economic Ties: A Quest for More Trade and Investment - (:unkn) unknown (My University, 2024)
This paper examines United States-African economic relations, focusing on trade and investment. It reviews historical and contemporary interactions, arguing that the engagement of the United States in Africa has largely been constrained by geopolitical factors, resulting in trade and investment levels that fall short of expectations. To enhance these connections, American and African policymakers need to reevaluate strategies, including developing policy frameworks to make Africa more attractive for investment and trade, leveraging the African Continental Free Trade Area (AfCFTA), aligning with existing initiatives, and mobilizing resources from the African diaspora in the United States.
Keywords: African Research